High‐Energy/Power and Low‐Temperature Cathode for Sodium‐Ion Batteries: In Situ XRD Study and Superior Full‐Cell Performance - Guo, Jin‐Zhi; Wang, Peng‐Fei; Wu, Xing‐Long; Zhang, Xiao‐Hua; Yan, Qingyu; Chen, Hong; Zhang, Jing‐Ping; Guo, Yu‐Guo (Advanced materials (Weinheim), 2017)
Sodium‐ion batteries (SIBs) are still confronted with several major challenges, including low energy and power densities, short‐term cycle life, and poor low‐temperature performance, which severely hinder their practical applications. Here, a high‐voltage cathode composed of Na3V2(PO4)2O2F nano‐tetraprisms (NVPF‐NTP) is proposed to enhance the energy density of SIBs. The prepared NVPF‐NTP exhibits two high working plateaux at about 4.01 and 3.60 V versus the Na+/Na with a specific capacity of 127.8 mA h g−1. The energy density of NVPF‐NTP reaches up to 486 W h kg−1, which is higher than the majority of other cathode materials previously reported for SIBs. Moreover, due to the low strain (≈2.56% volumetric variation) and superior Na transport kinetics in Na intercalation/extraction processes, as demonstrated by in situ X‐ray diffraction, galvanostatic intermittent titration technique, and cyclic voltammetry at varied scan rates, the NVPF‐NTP shows long‐term cycle life, superior low‐temperature performance, and outstanding high‐rate capabilities. The comparison of Ragone plots further discloses that NVPF‐NTP presents the best power performance among the state‐of‐the‐art cathode materials for SIBs. More importantly, when coupled with an Sb‐based anode, the fabricated sodium‐ion full‐cells also exhibit excellent rate and cycling performances, thus providing a preview of their practical application. A high‐voltage sodium‐super‐ion‐conductor‐type cathode significantly enhances the energy density of sodium‐ion batteries. Its low‐strain crystal lattice during the successive (de‐)sodiation and superior Na transport kinetics promise high‐rate capabilities, long‐term cycle life, superior low‐temperature performance, and excellent full‐cell performance, providing a preview of their practical applications.